(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review discusses modern approaches to the early detection and treatment of cervical dysplasia, focusing on recent developments in diagnostic methods and evidence-based treatment strategies. Advances in molecular diagnostics, such as human papillomavirus genotyping and biomarker analysis, have improved screening and risk assessment. Treatment options include careful observation and minimally invasive surgical procedures, chosen based on the severity of the condition, the patient’s age, reproductive plans, and human papillomavirus status. Recent studies support a personalized approach that aims to prevent cancer while preserving reproductive health. This summary brings together the latest clinical research and official recommendations for effective management of cervical dysplasia.